"دراسة اقتصادية للتوضّعات الرسوبية الحديثة في الجزء الأدنى من حوض نهر الكبير الشمالي" - سلمان, ندى; البب, سامر; زرزر, بانة (Latakia University Journal -Biological Sciences Series, 2019)
The sedimentary deposits in two sites (Rwaset Al-hresh, Rwaset Al-gzlan) of the lower part of Al-Kabir Al-Shimali basin Riveris have been studied from an economic perspective.. XRF and DNAA methods were used for chemical analyses. Grain structure measurement was also used to classify grain size of the studied samples. The importance of these deposits as a raw ore wasthat can be invested has been evaluated, as well. This study has revealed that these deposits in both many different sites could be used as a raw ores for international cement industry as well as Syrian standards after adding a certain portion of calcium oxide component. The research has shown that . The significant importance of this raw materials lies in the fact that all its components are used in cement industry. Moreover, tthe raw ores in those sites absolutely lacks the many harmful existence of small amounts of sulfate components which affects the quality of the cement., especially the sulfate. تعديل تمّ إجراء دراسة اقتصادية للتوضعات الرسوبية في الجزء الأدنى من حوض نهر الكبير الشمالي (موقعا رويسة الغزلان ورويسة الحرش(، حيث استخدم كل من جهازي التحليل الكيميائي بالأشعة المفلورة (XRF) والتنشيط النيوتروني(DNAA) في دراسة هذه التوضعات بالإضافة إلى تحديد التركيب الحبي لها.، وقُيّمت درجة أهمية التوضعات المدروسةتها كخام طبيعي قابل للاستثمار لاحقاً،. وتبيّن أنّها التوضعات المدروسة تصلح لأن تكون مادة أولية لصناعة الاسمنت بمواصفات عالمية وسورية وذلك في الموقعين المذكورين أكثر من موقع من المواقع المدروسة بعد إضافة أكسيد الكالسيوم إلى النسبة المطلوبة. بيّنت النتائج أنّ الخام الموجود في منطقة الدراسة يخلو تماما من مركبات الكبريت الضارة التي يؤثر وجودها في الخام على جودة الاسمنت.